2016
DOI: 10.15688/jvolsu1.2016.5.7
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modeling of Radiation Fields in Biological Tissues: the Definition of the Brightness Temperature for the Diagnosis

Abstract: The article contains the results of modeling of temperature fields and radiation fields in biological tissues. Experiments aimed at improving the efficiency of medical diagnosis of cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…These calculated data very closely match the model of the heat balance of biological tissues given in another study [27]. Experiments with thermal sensors implanted in the brain have shown that selective cerebral hypothermia in monkeys is reproduced when the scalp is cooled [28].…”
Section: Temperature Balance Of the Brain And Cchsupporting
confidence: 83%
“…These calculated data very closely match the model of the heat balance of biological tissues given in another study [27]. Experiments with thermal sensors implanted in the brain have shown that selective cerebral hypothermia in monkeys is reproduced when the scalp is cooled [28].…”
Section: Temperature Balance Of the Brain And Cchsupporting
confidence: 83%
“…We can use this method to construct vector 3D models of samples that are necessary for theoretical modeling physical processes in highly heterogeneous biological tissues [18,21]. Such 3D models allow to take into account the fine structure of real tissues and changes in their physical parameters.…”
Section: Examples Of Images Reconstruction In Arbitrary Sectionsmentioning
confidence: 99%